(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Tourism is one of the fastest-growing and most visible sectors of the global economy, contributing significantly to boosting a nation’s economy. Currently, tourism-led economic growth considering sustainable approaches is becoming increasingly important in public policy. Recent urban and regional studies have begun to focus on the sustainability of tourism from social, economic, environmental, and cultural perspectives. The research aims to identify the most important issues and barriers to sustainable tourism development in Uzbekistan and proposes the most effective culturalization strategies to overcome those barriers